Educational Concepts in Improving Arabic According to KH. Imam Zarkasyi - Mohammad Ismail; Rahmadin Ariga; Amir Reza Kusuma (al-Afkar, Journal For Islamic Studies, 2024)
Pondok Modern Darussalam Gontor (PMDG) is one of the well-known Islamic boarding school-based educational institutions in Indonesia. This research aims to ensure that the learning process in improving language skills can provide good results and achievements for students. Apart from that, it is also supported by the existence of Gontor entrance guidance institutions and Islamic boarding schools founded by its alumni. This is a very effective marketing channel. The learning process must be accompanied by study strategies, learning strategies, and language skills strategies including listening skills, speaking skills, reading skills and writing skills. KH Imam Zarkasyi said, "Actually we teach Arabic not because Arabic is the main goal. However, the real purpose of teaching Arabic is character building.